Impact of the synthesis method on the solid-state charge transport of radical polymers. Issue 1 (8th December 2017) - Zhang, Yiren; Park, Albert; Cintora, Alicia; McMillan, Stephen R.; Harmon, Nicholas J.; Moehle, Austin; Flatté, Michael E.; Fuchs, Gregory D.; Ober, Christopher K.
Abstract : Though poly(2, 2, 6, 6-tetramethylpiperidinyloxy methacrylate) (PTMA) was reported to be conductive, careful measurements indicate its insulating nature regardless of synthesis method, which have implication for its application in organic electronics. Abstract : There are conflicting reports in the literature about the presence of room temperature conductivity in poly(2, 2, 6, 6-tetramethylpiperidinyloxy methacrylate) (PTMA), a redox active polymer with radical groups pendent to an insulating backbone. To understand the variability in the findings across the literature and synthetic methods, we prepared PTMA using three living methods – anionic, ATRP and RAFT polymerization. We find that all three synthetic methods produce PTMA with radical yields of 70–80%, controlled molecular weight, and low dispersity. Additionally, we used on-chip EPR to probe the robustness of radical content in solid films under ambient air and light, and found negligible change in the radical content over time. Electrically, we found that PTMA is highly insulating – conductivity in the range 10 −11 S cm −1 – regardless of the synthetic method of preparation. These findings provide greater clarity for potential applications of PTMA in energy storage.